Anticipatory Risk Planning at PT Telkom Indonesia - Yusran, Muhammad; Hadijah, Sitti; Jumardi, Jumardi; Ilham, Bahrul Ulum (PT Inovasi Pratama Internasional, 2025)
This study examines the anticipatory risk management strategies implemented by PT Telkom Indonesia to address potential crises, including pandemics. This research aims to explore how a company can proactively identify, analyze, and manage risks to maintain service stability. Employing the Narrative Literature Review (NLR) approach, this study gathers and analyzes secondary data from various risk-management-related literature, focusing on the telecommunications sector. The findings reveal that although PT Telkom Indonesia has established risk strategies, several areas require further development, particularly in terms of long-term risk anticipation. This study recommends strengthening a more comprehensive and adaptive risk-management system to enhance corporate resilience. The originality of this research lies in its specific focus on PT Telkom Indonesia as a case study, highlighting the unique challenges and opportunities faced by a leading telecommunications company to address uncertainties and future crises. Additionally, this study contributes to the existing body of literature by providing insights into the application of anticipatory risk management in the telecommunications sector, particularly in the context of future pandemics.